Organizational culture and its influence on the adoption of digital technologies in the hotel industry (Journal SCIENCEVOLUTION, 2024)
In the digital age, adopting technologies is crucial for the competitiveness in the hotel sector. This study examines how organizational culture influences the adoption of digital technologies in hotels in Coronel Bogado, Paraguay. An exploratory methodology was used, with structured surveys conducted with owners and employees of 10 hotels. The results reveal that technological innovation is not actively encouraged in most hotels, and the main challenges include the high cost of technologies and the lack of skills. However, the perceived benefits include improvements in customer experience and hotel competitiveness. The research concludes that an organizational culture that actively promotes technological innovation is essential for the effective and sustainable adoption of digital technologies in the hotel sector of Coronel Bogado.
Keywords: Organizational culture; Digital technologies; Hotels; Competitiveness; Technological innovation